2022
DOI: 10.3389/fnut.2022.894966
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Children's Dietary Inflammatory Index (C-DII) and Markers of Inflammation and Oxidative Stress Among Children and Adolescents: NHANES 2015-2018

Abstract: ObjectivesTo explore the association of Children's Dietary Inflammatory Index (C-DII) scores with inflammation and markers of inflammatory factors in children and adolescents.MethodsData on dietary nutrient intake, markers of inflammation (ferritin, alkaline phosphatase, C-reactive protein (CRP), absolute neutrophil cell count and lymphocyte count) and oxidative stress (serum bilirubin, albumin, and iron) were available for participants aged 6–19 years (n = 1281). Each participant's C-DII score was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The study performed by Zhang X et al. demonstrated that the level of DII was significantly positively correlated with SBP and DBP [ 46 ]. In the present study, we demonstrated that patients in the highest DII tertiles group had lower SBP and DBP in the male S0 group.…”
Section: Discussionmentioning
confidence: 99%
“…The study performed by Zhang X et al. demonstrated that the level of DII was significantly positively correlated with SBP and DBP [ 46 ]. In the present study, we demonstrated that patients in the highest DII tertiles group had lower SBP and DBP in the male S0 group.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the absolute value of DII, the stronger the effect of diet on inflammation. DII has been reported to strongly correlate with many chronic diseases, such as coronary heart disease [ 18 ], metabolic syndrome [ 19 ], cancer [ 20 ], and osteoarthritis [ 21 ]. Studies demonstrated that a low DII diet was related to improved BMD in postmenopausal women of different races [ 22–24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has prompted research into developing a literature-derived index to reflect the inflammatory potential of diets; the Dietary Inflammatory Index (DII) [ 19 ] scores an individual’s diet on a continuum from anti- to pro-inflammatory. A pro-inflammatory diet has been linked to an increased cardiovascular risk and mortality [ 20 ], and it increases the likelihood of both metabolic syndrome (MetS) [ 21 ] and various types of cancer [ 22 , 23 , 24 , 25 ]. Recent studies indicate a negative association between a pro-inflammatory diet and HRQoL [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%